Esophageal Cancer and Beyond (IntechOpen, 2023)
Human life relies on two basic supplies from nature: oxygen and food. Oxygen can be utilized directly, but food has to go through a process of digestion to become usable nutrients. The esophagus represents the beginning of this long journey. Because of its critical location, esophageal cancer is one of the deadliest malignancies in the world, and furthermore its incidence has been rising steadily year after year while other cancers are declining. It is predicted that by the year 2035 the esophageal cancer population will increase by 77.4% and become one of top global concerns. This book covers many aspects of esophageal cancer, through which we hope to raise the awareness of professionals as well as non-professionals about this disease.